Management of Metastatic Spinal Cord Compression. Issue 9 (September 2017) - Sodji, Quaovi; Kaminski, Joseph; Willey, Christopher; Kim, Nathan; Mourad, Waleed; Vender, John; Dasher, Byron
Abstract : Abstract: Cancer metastasis is a key event in tumor progression associated not only with mortality but also significant morbidity. Metastatic disease can promote end-organ dysfunction and even failure through mass effect compression of various vital organs including the spinal cord. In such cases, prompt medical attention is needed to restore neurological function, relieve pain, and prevent permanent damage. The three therapeutic approaches to managing metastatic spinal cord compression include corticosteroids, surgery, and radiation therapy. Although each may improve patients' symptoms, their combination has yielded the best outcome. In cancer patients with clinical suspicion of spinal cord compression, dexamethasone should be initiated followed by surgical decompression, when possible, and radiation. The latter becomes the preferred treatment in patients with inoperable disease. Abstract : Metastatic spinal cord compression (MSCC) is the main cause of malignancy-induced spinal cord compression. Management of the condition includes corticosteroids, surgery, and radiation therapy. With progress in the field of radiation oncology, new techniques such as intensity-modulated radiation therapy and stereotactic body radiotherapy have become available for optimal treatment. This review provides an overview of MSCC and the roles of intensity-modulated radiation therapy and stereotactic body radiotherapy in the management of MSCC.